A Case of Brain Metastases from Breast Cancer Treated with Whole-Brain Radiotherapy and Eribulin Mesylate. (16th August 2012) - Nieder, Carsten; Aandahl, Gro; Dalhaug, Astrid
Abstract : Patients with triple receptor-negative breast cancer often develop aggressive metastatic disease, which also might involve the brain. In many cases, systemic and local treatment is needed. It is important to consider the toxicity of chemo- and radiotherapy, especially when newly approved drugs become available. Randomised studies leading to drug approval often exclude patients with newly diagnosed brain metastases. Here we report our initial experience with eribulin mesylate and whole-brain radiotherapy (WBRT) in a heavily pretreated patient with multiple brain, lung, and bone metastases from triple receptor-negative breast cancer. Eribulin mesylate was given after 4 previous lines for metastatic disease. Two weeks after the initial dose, that is, during the first cycle, the patient was diagnosed with 5 brain metastases with a maximum size of approximately 4.5 cm. She continued chemotherapy and received concomitant WBRT with 10 fractions of 3 Gy. After 3 cycles of eribulin mesylate, treatment was discontinued because of newly diagnosed liver metastases and progression in the lungs. No unexpected acute toxicity was observed. The only relevant adverse reactions were haematological events after the third cycle (haemoglobin 9.5 g/dL, leukocytes 3.1 × 10 9 /L). The patient died from respiratory failure 18.5 months from diagnosis of metastatic disease, and 2.7 months from diagnosis of brain metastases. To the best of our knowledge, this is the first report on combined WBRT and eribulin mesylate.